2013
DOI: 10.1017/s0022029913000101
|View full text |Cite
|
Sign up to set email alerts
|

Crude glycerol as glycogenic precursor in feed; effects on milk coagulation properties and metabolic profiles of dairy cows

Abstract: As grain prices rise, the search for alternative glycogenic precursors in animal feed becomes increasingly important, and this study was conducted to determine if the replacement of starch with glycerol, as an alternative glycogenic precursor, affects the milk metabolic profile and milk coagulation ability, and therefore the quality of the milk. Eight primiparous mid-lactation Holstein cows were fed during a replicated 4 × 4 Latin square trial with four different isoenergetic rations: (1) control (T0) fed a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Authors have reported decreases in milk protein concentration with up to 3 kg/d of dietary glycerol (Harzia et al, 2013), whereas others have shown increases in milk protein (Kass et al, 2012;Wilbert et al, 2013). In the current study the milk protein concentration and the daily production of milk protein remained constant regardless of dietary treatment.…”
mentioning
confidence: 38%
See 1 more Smart Citation
“…Authors have reported decreases in milk protein concentration with up to 3 kg/d of dietary glycerol (Harzia et al, 2013), whereas others have shown increases in milk protein (Kass et al, 2012;Wilbert et al, 2013). In the current study the milk protein concentration and the daily production of milk protein remained constant regardless of dietary treatment.…”
mentioning
confidence: 38%
“…In fact, a lower concentration of dietary purified glycerin (3.1%) has been shown to increase milk yield and milk protein concentration (Bodarski et al, 2005). When crude glycerin (82.6% glycerol) was added up to 15.6% in diets for medium-yield cows, no changes were observed in milk production and quality (Harzia et al, 2013), evidencing no difference in results of studies using crude or purified glycerin, as reported by Omazic et al (2013). Altogether, these experiments indicate that purified or crude glycerin can be fed up to 15% of dietary DM to lactating cows without deleterious effects.…”
Section: Introductionmentioning
confidence: 68%
“…Various studies Farkašová et al, 2007;Wang et al, 2009a;Harzia et al, 2013) indicate that glycerol changes the concentration of individual volatile fatty acids in the rumen, increases the content of propionate and butyrate, and decreases the amount of acetate. In both experiments of our study, the propylene glycol groups showed a numerically higher concentration of acetate and lower concentration of propionate and butyrate as compared with animals that received glycerol; however the differences between groups were relatively small and insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is responsible for converting propionate from starch fermentation in the rumen, glucogenic amino acids, and glycerol from adipose triglycerides into glucose (HIPPEN et al 2008). HARZIA et al (2013) evaluated the replacement of starch with crude glycerin. Eight primiparous mid-lactation dairy cows were used in a replicated 4 x 4 Latin Square experiment with 21-d periods, having one square of rumen cannulated cows.…”
Section: Glycerolmentioning
confidence: 99%